Correlation between Body Mass Index and Physical Activity with Scoliosis in Young Adult - Eufrasia Victa Swastika Anggriasti; Maria Regina Rachmawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background: Scoliosis is a deformity of spine that has excessive lateral curve. The deformity could becaused by postural adaptation to an imbalance of local trunk muscles or by another risk factors. There are tworisk factors, that are obesity and physical activity, which have not been studied in Indonesia yet about theircorrelation with scoliosis The aim of this study was to analyze the relationship between body mass index andphysical activity with scoliosis in young adults.Method: Study design was cross sectional. The subjects were High School students in Depok, recruited byconsecutive non-random sampling. The body mass index (BMI) was measured by body weight (Kg)/bodyheight (m2). The intensity of physical activity measured subjectively by International Physical ActivityQuestionnaires (IPAQ). Detection of postural scoliosis was by inspection and palpation and the deviationmeasured by scoliometer. The data were presence in univariate and bivariate, analyzed by the Pearsen Chisquare.Results: This study conducted in 165 subjects, the mean of age was 16-17 years old. There was no correlationbetween BMI and scoliosis (p=0,11). However the higher intensity of physical activity has correlated with thelower frequency of scoliosis (p=0.00).Conclusions: The lower intensity of physical activity increase the frequency of the postural scoliosis, in theother hand there was no correlation between BMI and scoliosis in young adults.Keywords : Scoliosis, Obesity, Physical activity